Pro-inflammatory Cytokines and Their Receptors: Expression and Regulation in the Uterine Endometrium during the Estrous Cycle in Pigs - Inkyu Yoo; Minjeong Kim; Jisoo Han; Hwanhee Jang; Sun-Ho Choi; Hakhyun Ka (The Korean Society of Animal Reproduction and Biotechnology, 2016)
Pro-inflammatory cytokines, interleukin-1β (IL1B), IL6, and tumor necrosis factor-alpha (TNF), are known to play important roles in regulating the endometrial function in the uterus during the estrous cycle and pregnancy in several species. However, the expression and function of these cytokines and their receptors in the uterine endometrium during the estrous cycle have not been studied in pigs. Thus, this study determined the expression and regulation of IL1B, IL6, TNF and their respective receptors, IL1R1, IL1RAP, IL6R, GP130, TNFRSF1A, and TNFRSF1B during the estrous cycle in pigs. To analyze levels of each gene expression in the uterine endometrium we obtained from endometrial tissues on Days 0, 3, 6, 9, 12, 15, and 18 of the estrous cycle. Real-time RT-PCR analysis showed that levels of IL1B, IL1RAP, IL6R, GP130, TNF, TNFRSF1A, and TNFRSF1B mRNAs were highest on Day 15 or 18 of the estrous cycle, which corresponds to the proestrus period. Levels of IL1R1 were highest on Day 0, while levels of IL6 were biphasic with high levels on Day 6 and Day 15. The abundance of IL1B, IL6, IL6R, and TNF mRNAs was decreased by progesterone, while levels of GP130 were increased by progesterone in endometrial tissue explants. These results showed that expression of pro-inflammatory cytokines and their receptors changed stage-specifically during the estrous cycle and regulated by progesterone in the uterine endometrium in pigs, suggesting that these pro-inflammatory cytokines may be involved in the regulation endometrial function during the estrous cycle in pigs.